Functional restoration of the esophagus after peroral endoscopic myotomy for achalasia. - Cheal Wung Huh (PLoS ONE, 2017)
Peroral endoscopic myotomy (POEM) is a new efficacious treatment option for achalasia. We propose to define "esophageal remodeling" as the functional restoration of the esophagus that involves decreased lower esophageal sphincter (LES) pressure, recovery of esophageal body peristalsis, and reduction of luminal diameter. The aim of this study was to investigate "esophageal remodeling" after POEM for achalasia.We analyzed data from a prospectively collected database of POEM subjects, which included preoperative and 2-month postoperative Eckardt symptom scores, and results from esophageal high resolution manometry (HRM) and barium esophagogram (BE). We recruited 23 patients (13 male; mean age: 53.9 years) whose preoperative and postoperative HRM and BE results were available, from among 30 patients with achalasia who underwent POEM at two institutions between July 2013 and December 2015.All patients achieved clinical treatment success (Eckardt score≤3). Partial recovery of esophageal body peristalsis was noted in 1/5 patients with type I (20%), 6/11 with type II (54.5%), and 7/7 with type III (100%) achalasia after POEM. Pan-esophageal pressurization disappeared after POEM in 10/11 type II achalasia patients. The average diameter of the esophageal body after POEM was significantly decreased in all types of achalasia.POEM provided excellent clinical symptomatic relief and esophageal remodeling in terms of restoration of peristalsis and reduction in diameter of the esophageal body, especially in patients with type III achalasia.